Effect of indirect Γ-L and Γ-X transfer on the carrier dynamics of InGaP/InAlP multiple quantum wells - Menoni, Carmen S., author; Buccafusca, O., author; Marconi, Mario Carlos, author; Patel, Dineshchandra, author; Rocca, Jorge J., author; Robinson, G. Y., author; Goodnick, Stephen M., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1997)
Indirect Γ-L scattering within the well, and real space carrier transfer to the barrier X1c states are shown to significantly affect the carrier dynamics in In0.48Ga0.52P/In0.5Al0.5P multiple quantum wells. When carriers transfer to the indirect states occurs, the carrier dynamics is modified by the slow return of the carriers from the low mobility states to the well. As a result, the absorption recovery time increases by almost an order of magnitude. Carrier transfer to the indirect states also increases the carrier lifetime to values characteristic of indirect recombination.
Keywords: semiconductor quantum wells; indium compounds; gallium compounds; phosphorus compounds; aluminium compounds; scattering; carrier lifetime; absorption; band structure